Identification of novel candidate genes associated with cleft lip and palate using array comparative genomic hybridisation. Issue 2 (14th September 2007) - Osoegawa, K; Vessere, G M; Utami, K H; Mansilla, M A; Johnson, M K; Riley, B M; L'Heureux, J; Pfundt, R; Staaf, J; van der Vliet, W A; Lidral, A C; Schoenmakers, E F P M; et al.
Abstract : Aim and method: We analysed DNA samples isolated from individuals born with cleft lip and cleft palate to identify deletions and duplications of candidate gene loci using array comparative genomic hybridisation (array-CGH). Results: Of 83 syndromic cases analysed we identified one subject with a previously unknown 2.7 Mb deletion at 22q11.21 coinciding with the DiGeorge syndrome region. Eighteen of the syndromic cases had clinical features of Van der Woude syndrome and deletions were identified in five of these, all of which encompassed the interferon regulatory factor 6 ( IRF6 ) gene. In a series of 104 non-syndromic cases we found one subject with a 3.2 Mb deletion at chromosome 6q25.1–25.2 and another with a 2.2 Mb deletion at 10q26.11–26.13. Analyses of parental DNA demonstrated that the two deletion cases at 22q11.21 and 6q25.1–25.2 were de novo, while the deletion of 10q26.11–26.13 was inherited from the mother, who also has a cleft lip. These deletions appear likely to be causally associated with the phenotypes of the subjects. Estrogen receptor 1 ( ESR1 ) and fibroblast growth factor receptor 2 ( FGFR2 ) genes from the 6q25.1–25.2 and 10q26.11–26.13, respectively, were identified as likely causative genes using a gene prioritisation software. Conclusion: We have shown that array-CGH analysis of DNA samples derived from cleft lip and palate subjects is an efficient and productive method for identifying candidate chromosomal loci and genes, complementing traditional genetic mapping strategies.